Replacing power with flexible structure: implementing flexible deadlines to improve student learning experiences - Hills, Melissa; Peacock, Kim (My University, 2022)
Traditional course deadline policies uphold the myth of the “normal” student, assuming students face few and equal barriers to completing work on time. In contrast, flexible deadline policies acknowledge that students face unequal barriers and seek to mitigate them. Flexible deadline policies maintain structure while transferring some decision-making power from the instructor into the hands of the student. These practices align with current pedagogical movements in higher education that seek to empower all students to meet learning goals. This study explores student perspectives on, and use of, proactive extensions built into a recent university course. We compare extension use in low-stake, high-stake, individual, and team assignments; observe how extension use changed over the term; and examine student self-reported responses about the policy. Students unanimously agreed that the proactive extension policy was valuable to their learning. They reported that the proactive extensions enabled them to improve the quality of their work and to better manage their academic workloads, acting as self-regulated learners. They also frequently described reduced stress as a benefit. Extensions generally appeared to be used as needed rather than encouraging procrastination. Students also identified that the need to request extensions in other courses was a barrier. The instructor of this course also benefitted from implementing this policy. Faculty should consider implementing flexible deadline policies to improve student learning experiences and to contribute to a more equitable and inclusive learning environment.
Keywords: flexible deadlines; proactive extension; assessment; inclusion